Resistensi Antibiotik pada Infeksi Saluran Kemih Anak: Tinjauan Pustaka - Erdiana, Grace; Teng, Hendratno Halim (PT Kalbe Farma Tbk., 2025)
Urinary tract infection (UTI) is one of the most common infections in children. This infection occurs when bacteria from the urethra ascend into the urinary tract, causing an infection that extends from the urethra to the renal parenchyma. The etiology could be bacteria, virus, or fungi, mostly caused by Escherichia coli (E. coli). Urine culture is the gold standard for UTI diagnosis and to determine appropriate therapy, especially antibiotics. Antibiotic resistance is a global issue, as 80% of healthcare facilities prescribe antibiotics for treatment. The incidence of resistance is higher in developed countries than in non-developed countries, with the highest incidence occurring in children aged 0-5 years. Antibiotic resistance increases mortality and morbidity and is also associated with higher costs. In the case of ISK, E. coli is also the pathogen with the highest incidence of antibiotic resistance, which may be associated with inappropriate use of antibiotics. The ease of obtaining antibiotics without a doctor’s prescription and a history of previous antibiotic use are factors that contribute to antibiotic resistance.